2010
DOI: 10.1002/chem.200902098
|View full text |Cite
|
Sign up to set email alerts
|

Microspheres of Mixed Proteins

Abstract: This paper describes the synthesis of mixed proteinaceous microspheres (MPMs) by the sonochemical method. The current fundamental research follows the research of Suslick and co-workers who have developed a method by which high-intensity ultrasound is used to make aqueous suspensions of proteinaceous microcapsules filled with water-insoluble liquids.1 By using high-intensity ultrasound, we have synthesized microspheres made of a few different proteins. The three proteins used in the current experiments are bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The microbubbles are created in a short process that lasts 3 min. [18] Herein, an antibiotic drug, tetracycline (TTCL), [19][20][21][22] was encapsulated in BSA or casein microspheres. The TTCL antibiotic has a broad range of activity, is relatively safe, can be used by many routes of administration, and is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…The microbubbles are created in a short process that lasts 3 min. [18] Herein, an antibiotic drug, tetracycline (TTCL), [19][20][21][22] was encapsulated in BSA or casein microspheres. The TTCL antibiotic has a broad range of activity, is relatively safe, can be used by many routes of administration, and is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Micrometer-sized gas-or liquid-filled micro/ nanospheres can be produced from various kinds of proteins such as bovine serum albumin (BSA), [4][5][6] human serum albumin (HSA), [7] hemoglobin (Hb), [8] and from combination of proteins. [9] The mechanism of the sonochemical formation of protein microspheres (PMs) has been discussed previously. [10] The microspheres are formed by chemically crosslinking cysteine residues, which undergo oxidation by HO 2 radicals formed around a micron-sized gas bubble or a nonaqueous droplet.…”
mentioning
confidence: 99%
“…The creation of the RNA‐loaded microspheres was repeated by using a different concentration of RNA in the precursor solution. The preparation of t‐RNA‐loaded BSA microspheres followed the typical synthesis of PMs, as described previously 21. In brief, 6.7 mL of an organic solvent (dodecane (98.0% Fluka) or soya bean oil, canola oil, or olive oil) was layered over a 10 mL water solution of a 5% w/v BSA protein (bovine serum albumin protein, Sigma–Aldrich) and 1% w/v purified t‐RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Micrometer‐sized gas‐ or liquid‐filled microspheres could be produced for various kinds of proteins, such as bovine serum albumin (BSA),16–18 human serum albumin (HAS),19 and hemoglobin (Hb),20 by using an ultrasonic emulsification method. Moreover, we have recently shown that PMs could be produced from a mixture of two kinds of protein 21. The mechanism of the sonochemical formation of microspheres has been discussed previously 22–25.…”
Section: Introductionmentioning
confidence: 93%